A practical guide to early childhood studies graduate practitioner competencies - Bradbury, Aaron; Musgrave, Jackie; Perkins, Helen (Helen Marie) 1957- (Learning Matters, A Sage Publishing Company, 2023)
"What do the Early Childhood Studies Graduate Practitioner Competencies (GPCs) mean in practice? What do they look like in settings? This book brings you case studies as examples of good practice demonstrating all of the GPCs. Each chapter covers a specific competency and includes: A visualisation of the competency; Case studies to explore what each competency looks like in practice; [and] Expert commentary on each case study helping you to link theory to practice." --